TAMI-66. FUNCTIONAL ALTERATIONS IN CORTICAL PROCESSING OF SPEECH IN GLIOMA-INFILTRATED CORTEX. (12th November 2021) - Aabedi, alexander; Lipkin, Benjamin; Kaur, Jasleen; Kakaizada, Sofia; Young, Jacob; Lee, Anthony; Krishna, Saritha; Chang, Edward; Brang, David; Hervey-Jumper, Shawn
Abstract: INTRODUCTION: Recent developments in the biology of malignant gliomas have demonstrated that glioma cells interact with neurons through both paracrine signaling and electrochemical synapses. Glioma-neuron interactions consequently modulate the excitability of local neuronal circuits, and it is unclear the extent to which glioma-infiltrated cortex can meaningfully participate in neural computations. For example, gliomas may result in a local disorganization of activity that impedes the transient synchronization of neural oscillations. Alternatively, glioma-infiltrated cortex may retain the ability to engage in synchronized activity, in a manner similar to normal-appearing cortex, but exhibit other altered spatiotemporal patterns of activity with subsequent impact on cognitive processing. METHODS: Here, we acquired invasive electrophysiologic recordings to sample both normal-appearing and glioma-infiltrated cortex during speech initiation in order to measure language task-related circuit dynamics of IDH-wild-type glioblastoma patients. We then applied an information theoretical framework to directly compare the encoding capacity and decodability of signals arising from these regions. RESULTS: We find that glioma-infiltrated cortex engages in synchronous activity during task performance in a manner similar to normal-appearing cortex, but recruits a diffuse spatial network. On a temporal scale, we show that glioma-infiltrated cortex has lower capacity for information encoding when performing nuanced tasks such as speech production of monosyllabic versus polysyllabic words. As a result, temporal decoding strategies for distinguishing monosyllabic from polysyllabic words were feasible for signals arising from normal-appearing cortex, but not from glioma-infiltrated cortex. CONCLUSION: These findings inform our understanding of cognitive processing in patients with malignant gliomas and have implications for patient survival, neuromodulation, and prosthetics in patients with malignant gliomas.